2016
DOI: 10.1139/cjfas-2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

A state-space stock assessment model for northern cod, including under-reported catches and variable natural mortality rates

Abstract: A state-space assessment model for the northern cod (Gadus morhua) stock off southern Labrador and eastern Newfoundland is developed here. The model utilizes information from offshore trawl surveys, inshore acoustic surveys, fishery catch age compositions, partial fishery landings, and tagging. This is done using an approach that avoids the use of subjective data-weighting. Estimates of fishing mortality rates (F) are usually conditional on assumptions about natural mortality rates (M) in stock assessment mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 39 publications
1
60
0
Order By: Relevance
“…It is also possible that immigration of fish occurred, most likely from Smith Sound. The sudden and not easily explained increases in both the DFO fall trawl survey (Cadigan 2016) and the present acoustic-trawl spring survey in 2008 with apparent decreases in mortality of ages 4-to 6-year-old cod occurred at the same time the Smith Sound cod were dispersing (Rose et al 2011;Cadigan 2016). Although no appropriate year-class data are available from Smith Sound for the early 2000s, it is plausible that these were relatively strong, because the 1990 and 1992 founder year-classes were abundant with substantial spawning potential in those years (Rose 2003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also possible that immigration of fish occurred, most likely from Smith Sound. The sudden and not easily explained increases in both the DFO fall trawl survey (Cadigan 2016) and the present acoustic-trawl spring survey in 2008 with apparent decreases in mortality of ages 4-to 6-year-old cod occurred at the same time the Smith Sound cod were dispersing (Rose et al 2011;Cadigan 2016). Although no appropriate year-class data are available from Smith Sound for the early 2000s, it is plausible that these were relatively strong, because the 1990 and 1992 founder year-classes were abundant with substantial spawning potential in those years (Rose 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, both the fall trawl survey of (the Department of) Fisheries and Oceans Canada (DFO) and the winter acoustictrawl survey reported here showed an increase in cod biomass in the Bonavista Corridor that was difficult to explain by local production alone. Recently, a modelling study examined that disparity by including acoustic-trawl survey data from Smith Sound and an assumption that maturing fish regrouped with the Bonavista Corridor cod after 2007 (Cadigan 2016). In effect, doing so changed the catchability (q) of the main DFO trawl survey over time, with a model that fit most existing data better and further suggested that northern cod spawning biomass may have been underestimated in recent years based on the fall trawl survey alone.…”
Section: Introductionmentioning
confidence: 99%
“…AIC was used to determined the optimal observational likelihood, since the AIC estimates the Kullback-Liebler divergence between the candidate model and the true data generating system (Akaike 1974), i.e. the information lost by using the candidate model instead of the true data generating system (Burnham and Anderson 2002). The Kullback-Liebler divergence can not be used directly because the calculation requires full knowledge of the true data generating system.…”
Section: Discussionmentioning
confidence: 99%
“…The number of tags returned reflect exploitation on the tagged population whose size is known or can be estimated, whereas the size of the fishery catch reflects exploitation on a population of unknown size. Tagging experiments can provide important information on fishing and natural mortality rates that are difficult to estimate using standard catch and survey data used in fish stock assessment (Polacheck et al 2006;Cadigan 2015;Goethel et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…DFO 2013, 2015aCadigan 2015). Results of these tagging studies are reported annually in stock assessments.…”
Section: Introductionmentioning
confidence: 99%